TNM staging atlas with oncoanatomy - Rubin, Philip , 1927-; Hansen, John T. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
The Second Edition of TNM Staging Atlas with 3D Oncoanatomy has been updated to include all new cancer staging information from the Seventh Edition of the AJCC Cancer Staging Manual. The atlas presents cancer staging in a highly visual rapid-reference format, with clear full-color diagrams and TNM stages by organ site. The illustrations some original and some derived from Grant's Atlas of Anatomy are three-dimensional, three-planar cross-sectional presentations of primary anatomy and regional nodal anatomy. They show the anatomic features identifiable on physical and/or radiologic examination and the anatomic extent of cancer spread which is the basis for staging. A color code indicates the spectrum of cancer progression at primary sites (T) and lymph node regions (N). The text then rapidly reviews metastatic spread patterns and their incidence. For this edition, CT or MRI images have been added to all site-specific chapters to further detail cancer spread and help plan treatment. Staging charts have been updated to reflect changes in AJCC guidelines, and survival curves from AJCC have been added to site-specific chapters"--Provided by publisher.